1974
DOI: 10.1139/y74-041
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Cholecystokinin and Related Peptides on Guinea Pig Small Intestine

Abstract: The mode of action of cholecystokinin (CCK), an octapeptide fragment of CCK, caerulein, and pentagastrin on isolated guinea pig ileal muscle was investigated and their relative potencies determined. On a molar basis, octapeptide-CCK and caerulein were about twice as potent as CCK, whereas pentagastrin and Urecholine were respectively 23 and 46 times less potent. Scopolamine (6.84 × 10−4 M) inhibited the response to all four peptides relatively less than the response to Urecholine. Tetrodotoxin (0.1 μg/ml) inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 0 publications
2
20
0
2
Order By: Relevance
“…The administration of CCK-OP in 20-fold higher dose than that of cerulein, which is considered to be of similar potency (Romań ski, 2004), evoked, however, a stronger effect on the incidence of the MR as compared with the cerulein effect. Yau et al (1974) suggested that CCK-OP and cerulein are equipotent, while Ruckebusch and Soldani (1985) found that a 10-fold lower cerulein dose than CCK-OP evoked an even stronger gallbladder contractile response. These doses were similar to those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of CCK-OP in 20-fold higher dose than that of cerulein, which is considered to be of similar potency (Romań ski, 2004), evoked, however, a stronger effect on the incidence of the MR as compared with the cerulein effect. Yau et al (1974) suggested that CCK-OP and cerulein are equipotent, while Ruckebusch and Soldani (1985) found that a 10-fold lower cerulein dose than CCK-OP evoked an even stronger gallbladder contractile response. These doses were similar to those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that this CCK effect results from direct hormonal action on gallbladder musele (4,5). It has been proposed that this action of CCK on the gallbladder is physiological (6).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our data and that published in the literature we propose the following mechanisms. The excitatory respohses of the gall-bladder, small intestine, and Heidenhain pouch to CCK-7 and CCK were suppressed by atropine and ganglion blockers and were mediated, therefore, through release of acetylcholine, as has been demonstrated for isolated gallbladder and gastrointestinal smooth muscle (Yau & Farrar, 1972;Fisher, DiMarino & Cohen, 1973;Vizi, Bertaccini, Impicciatore & Knoll, 1973). The inhibitory effects of CCK-7 and CCK on the motility and spike discharges in stomach and duodenum (Doringer et al, 1975;Oigaard et al, 1975) are mediated not by adrenergic transmission but probably by other hormonal factors, e.g secretin, somatostatin or VIP, and this is supported by the following observations:…”
Section: Effects Of Various Drugs On Cck Responsesmentioning
confidence: 69%